Muslim consumer awareness towards Halal food product in Malaysia / Nurfarahetika Mohamed As'hari - Mohamed As'hari, Nurfarahetika (Faculty of Business Management, 2015)
Halal trend has become the lifestyle of a muslims consumers all over the world. Since Malaysia is leading towards the global halal hub, this research it is essential to give some ideas on Muslims consumers towards Halal food. The objective of this research is to measure the awareness towards halal food products in Malaysia which primarily a Muslim country. Given the importance responsibility of halal awareness as being a Muslims and their obligations to meet Shariah compliant, consequently, the research addresses to elucidate determinants on awareness towards halal food product in Malaysia. There are many factors bearing on the awareness of halal food products but on previous studies, it focused mostly on the halal certification logo. In order to load the void, this research proves that there are other factors that influence awareness towards halal food. Using the factor analysis, it shows that halal information, religious values, safety, health, exclusivity and marketing are the determinants on muslims’ awareness towards halal food product. Keywords : Awareness, Halal, Muslim Consumer, Food Product, Shariah Compliant.